2013
DOI: 10.1097/mlr.0b013e3182780917
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Provider Secure Messaging in VA

Abstract: In this exploratory analysis of early SM implementation in VA, we found a path of associations linking SM and reductions in UC utilization. These results suggest a need for further examination of the relationship between SM and its effects on health care utilization patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…Studies from 2013 also demonstrated several barriers to use of the patient portal; most common were lack of Internet access and lack of technical support [19,20,22,23]. Another significant finding in 2013 was the association of patient portal use with medication adherence, disease control, self-maintenance of health, and including the patient in the medical decision [16,19,22,23].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies from 2013 also demonstrated several barriers to use of the patient portal; most common were lack of Internet access and lack of technical support [19,20,22,23]. Another significant finding in 2013 was the association of patient portal use with medication adherence, disease control, self-maintenance of health, and including the patient in the medical decision [16,19,22,23].…”
Section: Resultsmentioning
confidence: 99%
“…Another significant finding in 2013 was the association of patient portal use with medication adherence, disease control, self-maintenance of health, and including the patient in the medical decision [16,19,22,23]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Health systems must allot providers enough time to address patient needs that arise electronically and consider incorporating a team-based workflow into secure electronic messaging. It is also unclear how secure electronic messaging will affect face-to-face visits in a safety-net setting given that prior studies demonstrate mixed impacts on in-person utilization (Bergmo, Kummervold, Gammon, & Dahl, 2005;Liss et al, 2014;Palen, Ross, Powers, & Xu, 2012;Shimada et al, 2013;Zhou, Garrido, Chin, Wiesenthal, & Liang, 2007). Finally, given the increasingly broad adoption of this medium across the United States, more studies are needed in varying care settings to elucidate the factors influencing utilization and content of electronic communication.…”
Section: Practical Implicationsmentioning
confidence: 99%